An Overview of Zoonotic Disease Outbreaks and its Forensic Management Over Time. Issue 5 (22nd February 2019) - Serrano, Isa; Gomes, Diana; Ramilo, David; Rebelo, Maria Teresa; da Fonseca, Isabel Pereira; Moreira, Anabela; Oliveira, Manuela
Abstract: Most emerging or re‐emerging infections are vector‐borne or zoonotic and can be disseminated worldwide by infected humans or animals. They are a major public health problem and cause a great impact on economy. Zoonotic outbreaks began to be characterized in the 90s, after the creation of Europol and the FBI. Such investigations are carried by forensic pathologists and other specialists to determine whether an outbreak is natural or deliberate. This review will discuss ten zoonotic outbreaks nonrelated to wars focusing on forensic management. In conclusion, some points should be highlighted in the management of a zoonotic outbreak: (i) its diagnosis and detection by forensic pathologists and the coordination of efforts between other specialists are key factors; (ii) communication guidelines and an efficient healthcare system are crucial for any emergency response; (iii) biosafety of all specialists involved must be guaranteed.